Pengaruh Minat Belajar dan Disiplin Belajar terhadap Prestasi siswa di MAN 2 Kabupaten Bekasi - Hasna Lathifah; Diva Yulianti; Iqbal Hasan Kamil; Millah Tazkiyyah; Uswatun Hasanah (Institut Nalanda, 2023)
In education, in order to achieve optimal learning achievement, there are factors that must be considered, namely factors of interest in learning and learning discipline. The purpose of this research was to determine the effect of learning interest and learning discipline together on student achievement. The method used in this study is a survey method with multiple linear regression analysis. The data collection carried out in the study was by distributing questionnaires. The population in this study were all 11th grade students, totaling 36 students. And the sample used is 30 students. Instrument validity test using SPSS version SPSS 16.0 and reliability test using Cronbach's Alpha of 0.905. Based on data analysis, it can be interpreted that there is a significant influence between learning interest on learning achievement Islamic Cultural History of 11th grade students majoring in Science in MAN 2 district. Bekasi. This is evidenced by the acquisition of Sig. = 0.006 <0.05 and t count = 2.980.